2022
DOI: 10.1007/s00787-022-02060-0
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the mental health changes of children and young people before and during the COVID-19 pandemic

Abstract: There is increasing knowledge that the COVID-19 pandemic has had an impact on mental health of children and young people. However, the global evidence of mental health changes before compared to during the COVID-19 pandemic focusing on children and young people has not been systematically reviewed. This systematic review examined longitudinal and repeated cross-sectional studies comparing before and during COVID-19 pandemic data to determine whether the mental health of children and young people had changed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
113
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(185 citation statements)
references
References 53 publications
7
113
0
3
Order By: Relevance
“…Scores for each subscale were classified into five severity ranges: normal, mild, moderate, severe, and extremely severe. The cut-off points for each category were as follows: for depression subscale, normal (0-9), mild (10)(11)(12)(13), moderate (14)(15)(16)(17)(18)(19)(20), severe (21)(22)(23)(24)(25)(26)(27), and extremely severe (28 and more); for anxiety subscale, normal (0-7), mild (8)(9), moderate (10)(11)(12)(13)(14), severe (15)(16)(17)(18)(19), and extremely severe (20 and more); for the Stress subscale, normal (0-14), mild (15)(16)(17)(18), moderate (19)(20)(21)(22)(23)(24)(25), severe (26)(27)(28)(29)(30)(31)(32...…”
Section: Research Instruments and Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scores for each subscale were classified into five severity ranges: normal, mild, moderate, severe, and extremely severe. The cut-off points for each category were as follows: for depression subscale, normal (0-9), mild (10)(11)(12)(13), moderate (14)(15)(16)(17)(18)(19)(20), severe (21)(22)(23)(24)(25)(26)(27), and extremely severe (28 and more); for anxiety subscale, normal (0-7), mild (8)(9), moderate (10)(11)(12)(13)(14), severe (15)(16)(17)(18)(19), and extremely severe (20 and more); for the Stress subscale, normal (0-14), mild (15)(16)(17)(18), moderate (19)(20)(21)(22)(23)(24)(25), severe (26)(27)(28)(29)(30)(31)(32...…”
Section: Research Instruments and Measurementsmentioning
confidence: 99%
“… 9 Furthermore, systematic review and meta-analysis results revealed that COVID-19 poses mental health risks to young people and college students. 10 , 11 According to Li et al, depression and anxiety significantly increased during the COVID-19 pandemic among college students.…”
Section: Introductionmentioning
confidence: 99%
“…There are now several longitudinal studies of change in mental health measures among children and young adults before and during the COVID-19 pandemic [22]. Several comprehensive studies of college and university students in the United States include data on prepandemic mental health, analyses of predictors, and a focus on serious psychiatric and alcohol/drug use outcomes [23,24], but data are lacking for high school students.…”
Section: Plos Onementioning
confidence: 99%
“…In this sense, multiple studies have already assessed the changes in mental health generated in different populations and countries, as well as the risk and protective factors that influence this response, showing a very high impact in general. However, there are clear differences depending on the studied population characteristics (age group, gender, country) and the previous coping capacity and resilience, and also to the lockdown conditions [ 2 , 3 , 4 ]. Among university students, it has been observed that the impact on their mental health was even greater [ 5 , 6 ], possibly since this is a population with high rates of psychological distress [ 7 ].…”
Section: Introductionmentioning
confidence: 99%